EFFECT OF SPIRITUAL NURSING CARE ON THE LEVEL OF ANXIETY IN PATIENTS WITH STROKE - Bernadeta Trihandini; Diyah Fatmasari; Lucia Endang Hartati YK; Sudirman Sudirman (Belitung Raya Foundation, Indonesia, 2018)
Background: Anxiety in stroke patients occurs as a normal reaction to stress with life changes; however, when it becomes excessive, it will be disorder. Effort to deal with anxiety is needed and spiritual approach nursing care is considered useful in caring patients with stroke. Objective: To examine the effect of spiritual nursing care on anxiety in stroke patients in the inpatient ward. Methods: This study used a quasi-experimental design with pretest-posttest control group. Thirty respondents were selected using consecutive sampling, which 15 respondents assigned in the experiment and control group. The Hamilton Anxiety Rating Scale was used to measure anxiety. Data were analyzed using paired t-test and independent t-test. Results: The results showed that the mean level of anxiety in the experiment group before intervention was 29.33 and decreased to 9 after intervention, while in the control group the mean level of anxiety before intervention was 29.47 and decreased to 17.73 after intervention. Paired t-test obtained p-value 0.000 (<0.05), which indicated that there was a significant effect of spiritual nursing care on anxiety levels in patients with stroke. Conclusion: Spiritual nursing care could reduce anxiety in patients with stroke.